2018
DOI: 10.1155/2018/7352691
|View full text |Cite
|
Sign up to set email alerts
|

A Point Cloud Registration Algorithm Based on Feature Extraction and Matching

Abstract: The existing registration algorithms suffer from low precision and slow speed when registering a large amount of point cloud data. In this paper, we propose a point cloud registration algorithm based on feature extraction and matching; the algorithm helps alleviate problems of precision and speed. In the rough registration stage, the algorithm extracts feature points based on the judgment of retention points and bumps, which improves the speed of feature point extraction. In the registration process, FPFH feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…erefore, many modifications related to the NDT algorithm were proposed by researchers. For example, Yong et al [201] introduced an improved normal distribution transform algorithm in a precise registration step. In this method, PDF is replaced by a mixed probability density function.…”
Section: Normal Distributionmentioning
confidence: 99%
“…erefore, many modifications related to the NDT algorithm were proposed by researchers. For example, Yong et al [201] introduced an improved normal distribution transform algorithm in a precise registration step. In this method, PDF is replaced by a mixed probability density function.…”
Section: Normal Distributionmentioning
confidence: 99%
“…However, in the presented work, it is suggested that the objective function incorporates ego-motion estimation with uncertainty, thus its performance is revealed to be more accurate under feature-poor and self-similar environments. In 2018, Liu et al [ 22 ] proposed an Improved NDT (INDT) that registers using fractional pre-processed feature points only. For this, the work applied a Fast Point Feature Histogram (FPFH) descriptor and Hausdorff distance method to extract feature points.…”
Section: Related Workmentioning
confidence: 99%
“…The adapted score function of the proposed algorithm has similarities with the previous reference [ 21 ], yet the objective function employs a unique classifier coefficient depending on point characteristics. The INDT approach in [ 22 ] also extracts and uses feature points during the scan matching procedure, yet differs from the proposed methods in that extracted feature points are only used for the registration process. Due to this reasoning, the INDT in [ 22 ] is excluded from the performance comparison algorithm because poor performance is achieved through INDT with a relatively smaller number of feature points for the 2D measurement environment.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments show that this method achieved better robustness in nonrigid registration. In recent years, under the framework of EM algorithm optimization, some robust point set registration algorithms have been proposed [10,12,13].…”
Section: Introductionmentioning
confidence: 99%